2001
DOI: 10.1086/323691
|View full text |Cite
|
Sign up to set email alerts
|

Heating and Ionization of the Intergalactic Medium by an Early X‐Ray Background

Abstract: Observational studies indicate that the intergalactic medium (IGM) is highly ionized up to redshifts just over 6. A number of models have been developed to describe the process of reionization and the e †ects of the ionizing photons from the Ðrst luminous objects. In this paper we study the impact of an X-ray background, such as high-energy photons from early quasars, on the temperature and ionization of the IGM prior to reionization, before the fully ionized bubbles associated with individual sources have ove… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
213
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(214 citation statements)
references
References 58 publications
1
213
0
Order By: Relevance
“…Häring & Rix 2004) by gas accretion (Islam et al 2003). The inferred presence of pregalactic IMBHs and their associated accretion luminosity has been a source of intense speculation with regard to a mechanism for the reionization of the universe (e.g., Madau et al 2004;Ricotti & Ostriker 2004;Venkatesan et al 2001). Our results place these speculations on a sounder footing.…”
Section: Discussion and Future Workmentioning
confidence: 52%
“…Häring & Rix 2004) by gas accretion (Islam et al 2003). The inferred presence of pregalactic IMBHs and their associated accretion luminosity has been a source of intense speculation with regard to a mechanism for the reionization of the universe (e.g., Madau et al 2004;Ricotti & Ostriker 2004;Venkatesan et al 2001). Our results place these speculations on a sounder footing.…”
Section: Discussion and Future Workmentioning
confidence: 52%
“…If the gas temperature is fixed to the CMB temperature, then the Jeans mass, M j ¼ 10 6 M . If molecular hydrogen is available, then the Jeans mass before reionization is M j 0 $ 2:2 Â 10 3 ½w b =hðw m Þ 1:5 ð1 þ zÞ=10 for z < 150 (Venkatesan et al 2001). At z > 150, the electrons are thermally coupled to the CMB photons.…”
Section: Reionization and Small-scale Powermentioning
confidence: 99%
“…They suggest using a minimum mass that is much higher: M HRL min ðzÞ ¼ 10 8 ð1 þ zÞ=10 ½ À3=2 . On the other hand, if the first stars generated a significant flux of X-rays (Oh 2001), then this would have promoted molecular hydrogen formation (Haiman et al 2000;Venkatesan et al 2001;Cen 2002), thus lowering the minimum mass back to M j .…”
Section: Reionization and Small-scale Powermentioning
confidence: 99%
“…The free-free emission from the hot (T $ 10 6 10 8 K) SNR leads to soft X-ray emission. It has been suggested that positive feedback, in terms of molecular hydrogen formation, is possible if an early X-ray background builds up (Haiman et al 2000;Oh 2002;Venkatesan et al 2001;see, however, a counterargument by Machacek et al 2003). Population III supernova remnants are therefore among the most plausible X-ray sources in the early universe ).…”
Section: Supernov Va Feedbackmentioning
confidence: 99%